Microemulsion: New Insights into the Ocular Drug Delivery. (27th June 2013) - Hegde, Rahul Rama; Verma, Anurag; Ghosh, Amitava
Abstract : Delivery of drugs into eyes using conventional drug delivery systems, such as solutions, is a considerable challenge to the treatment of ocular diseases. Drug loss from the ocular surface by lachrymal fluid secretion, lachrymal fluid-eye barriers, and blood-ocular barriers are main obstacles. A number of ophthalmic drug delivery carriers have been made to improve the bioavailability and to prolong the residence time of drugs applied topically onto the eye. The potential use of microemulsions as an ocular drug delivery carrier offers several favorable pharmaceutical and biopharmaceutical properties such as their excellent thermodynamic stability, phase transition to liquid-crystal state, very low surface tension, and small droplet size, which may result in improved ocular drug retention, extended duration of action, high ocular absorption, and permeation of loaded drugs. Further, both lipophilic and hydrophilic characteristics are present in microemulsions, so that the loaded drugs can diffuse passively as well get significantly partitioned in the variable lipophilic-hydrophilic corneal barrier. This review will provide an insight into previous studies on microemulsions for ocular delivery of drugs using various nonionic surfactants, cosurfactants, and associated irritation potential on the ocular surface. The reported in vivo experiments have shown a delayed effect of drug incorporated in microemulsion and an increase in the corneal permeation of the drug.